Analysis of students' dual processes in solving number pattern questions and providing scaffolding - Ganis Irma Firnanda; Susiswo (Journal Focus Action of Research Mathematic (Factor M), 2024)
This research aims to describe students' dual-process in solving number pattern questions and scaffolding that support students' dual-process. This research uses a qualitative research approach with a case study type. The subjects of this research were two 10th grade high school students. The subjects' written answers, recorded interviews, and researcher notes were used as the basis to analyze the subjects' dual-process and scaffolding. There are three findings from this research. First, subjects tend to activate mental processes that are automatic, subjective-empirical, and often occur unconsciously in solving number pattern questions. Second, errors occur due to the subject's tendency towards one of the mental processes which are automatic, subjective-empirical, and often occur unconsciously. Third, scaffolding in the form of questions and instructions by the researcher supports the activeness of the subject's mental processes which are empirically accurate and involve deeper consideration more thorough analysis, and greater consciousness in decision-making, thereby helping the subject correct his mistakes when solving number pattern questions. The findings of this research indicate that the tendency to activate mental processes that are automatic, subjective-empirical, and often occur unconsciously can cause disadvantages. Therefore, the learning process needs strategies that support students to optimize both mental processes. Teacher training that focuses on learning strategies that support students to optimize the use of both mental processes needs to be held regularly.